1991
DOI: 10.2337/diacare.14.2.138
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Glucose and Insulin Responses to Mixed Meal in Type II Diabetic Patients

Abstract: These results suggest that glucose and insulin responses to a test meal are reproducible in type II diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Low GI foods include vegetables, fruit, legumes and wholegrain breads such as pumpernickel, while high-GI foods include most refined grain products such as white bread, potatoes and rice (Table 2). The GI tables may have various applications, for instance in designing diets aimed at long-term blood glucose control, as some researchers have found that the GI may be applied not only to single foods but also to mixed meals (Wolever et al, 1985;Chew et al, 1985;Collier et al, 1986;Bornet et al, 1987;Le Floch et al, 1991). The GI of mixed meals has also been shown to correlate positively with the insulinemic index (a measure of postprandial insulin rise; Bornet et al, 1987).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
“…Low GI foods include vegetables, fruit, legumes and wholegrain breads such as pumpernickel, while high-GI foods include most refined grain products such as white bread, potatoes and rice (Table 2). The GI tables may have various applications, for instance in designing diets aimed at long-term blood glucose control, as some researchers have found that the GI may be applied not only to single foods but also to mixed meals (Wolever et al, 1985;Chew et al, 1985;Collier et al, 1986;Bornet et al, 1987;Le Floch et al, 1991). The GI of mixed meals has also been shown to correlate positively with the insulinemic index (a measure of postprandial insulin rise; Bornet et al, 1987).…”
Section: Glycemic Index and The Slow-release Carbohydratementioning
confidence: 99%
“…It has been suggested that a standardized, mixed test meal would be more efficient than an oral glucose tolerance test (OGTT) for assessing impaired glucose tolerance (IGT) or diabetes [1][2][3][4][5]. A postmeal glucose tolerance test may avoid the low acceptability of the glucose load and improve reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have found that the GI of individual foods does not predict the glycemic response when these foods are eaten as part of a mixed meal, 129,130 many have found that GI values can be used to accurately predict the effect of mixed meals on blood glucose levels. 20,85,[131][132][133][134][135][136] In the study by Alfenas and Mattes, 130 high and low GI foods were not compared in the same individuals, casting doubt on the accuracy of these findings.…”
Section: Cancermentioning
confidence: 99%